Rural Youth Entrepreneurship Capital and Potential Entrepreneurship - Ambara Purusottama (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This study aims to explore a region’s potential entrepreneurship which is an important asset for national economy. In addition, this research also measures the extent of the region’s potential entrepreneurship in the perspective of entrepreneurship capital. The survey was able to collect 901 valid questionnaires from youth respondents and analyzed using Structural Equation Modeling (SEM). The research findings show that from the four forms of entrepreneurship capital, only financial capital and cultural capital could bring about the region’s potential entrepreneurship or entrepreneurial intention. Other findings explain the striking difference between the perspective of youth people who were entrepreneurs and those who were workers. The youth entrepreneurs were able to convert the capital into entrepreneurial opportunities. While the youth workers even though they also had similar capital since they did not have the entrepreneurial ability, they failed to take advantage of the capital they had. The contribution of this research is to strengthen the concept of entrepreneurship capital from the resources-based perspective.